METHODOLOGY OF ORGANIZING GYMNASTICS EXERCISES IN PRIMARY CLASSES - Khaidarov Fakhriddin Farajillaevich (Academia Science Repository, 2023)
This article aims to develop a set of gymnastic exercises for elementary school students. The article discusses various aspects and methods of gymnastic exercises.